2022
DOI: 10.3390/toxics10020063
|View full text |Cite
|
Sign up to set email alerts
|

White-Tailed Eagles’ (Haliaeetus albicilla) Exposure to Anticoagulant Rodenticides and Causes of Poisoning in Poland (2018–2020)

Abstract: The white-tailed eagle (Haliaeetus albicilla) is strictly protected in Poland due to its threat of extinction. This study’s main goal was to assess their exposure to indirect poisoning by anticoagulant rodenticides (AR). This study presents the investigation results of 40 white-tailed eagles’ suspected poisoning cases in the years 2018–2020 in Poland. In all tested liver samples, using a liquid chromatography–mass spectrometry method, at least one of the AR (bromadiolone, brodifacoum, difenacoum, flocoumafen) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Regarding large eagles, Badry et al (2021) detected ARs in 38.3% of white-tailed sea eagles (Haliaeetus albicilla) (n = 60) in Germany. Sell et al (2022) detected SGARs in 100% of white-tailed sea eagles found dead with suspected poisoning (n = 40) in Poland. In France, Moriceau et al (2022) detected ARs in the liver of 100% of golden eagles found dead (n = 7).…”
Section: Discussionmentioning
confidence: 97%
“…Regarding large eagles, Badry et al (2021) detected ARs in 38.3% of white-tailed sea eagles (Haliaeetus albicilla) (n = 60) in Germany. Sell et al (2022) detected SGARs in 100% of white-tailed sea eagles found dead with suspected poisoning (n = 40) in Poland. In France, Moriceau et al (2022) detected ARs in the liver of 100% of golden eagles found dead (n = 7).…”
Section: Discussionmentioning
confidence: 97%
“…Overexploitation of agricultural lands, often used for monocultures, has led to the alteration of natural habitats. Moreover, pesticide use in agriculture leads to a reduction in trophic availability for insectivorous species as well as to possible toxic events [ 5 ]. All these jeopardise wildlife, with many animals needing to be rescued and taken to wildlife recovery centres.…”
Section: Introductionmentioning
confidence: 99%
“…The direct cause of death of the first individual was poisoning by anticoagulant rodenticides (individual no. #34, (Sell et al 2022 ). The second bird was found to have been exposed to anticoagulant rodenticides and carbofuran, which was considered the probable cause of death (individual no.…”
Section: Resultsmentioning
confidence: 99%
“…The sampling was performed by people dealing with raptor conservation (veterinarians, employees of the National State Forests, National Parks, and wildlife rescue centers). Collected liver samples were packed separately in labeled safe sampling bags or containers, frozen immediately, and sent to the Department of Pharmacology and Toxicology of the National Veterinary Research Institute in Puławy for toxicological diagnostics targeting residues of rodenticides and pesticides that are illegally used for pest control (Sell et al 2022 ). When possible, the information about the birds, including species, date of sampling, and location, was recorded by the sampler on the spot.…”
Section: Methodsmentioning
confidence: 99%